Awe: a putative mechanism underlying the effects of classic psychedelic-assisted psychotherapy. (4th July 2018) - Hendricks, Peter S.
Abstract: A psychological model of classic psychedelic-assisted psychotherapy informed by contemporary scientific data is presented in this paper. It is suggested that classic psychedelic-occasioned mystical experience is characterized by profound awe, a discrete emotion experienced in the presence of a vast stimulus requiring accommodation of mental structures. Awe, in turn, promotes the small self, a construct that, in the extreme, is analogous to those of unitive experience and ego dissolution. The small self is conceptualized as key to understanding the downstream effects of mystical experience occasioned in the context of classic psychedelic-assisted psychotherapy. With this novel theoretical framework in mind, a number of clinical implications and recommendations are provided so as to advance this incipient field of study.